Matrix Method for Modelling of Multicomponent and Multistream Energy Systems and Installations of Thermal Power Plants - Barochkin A.E. (Problems of the Regional Energetics)
The aim of this work is to increase the operational efficiency of the multicomponent multithreaded power units and systems of the TPP using modeling, calculation and optimization. The goal is achieved by solving the following tasks: development of the tasks’ classification system and a unified methodology for the mathematical description of energy formation and mass flows’ processes in multicomponent and multithreaded power units of the TPP; development of a model of a steam turbine power unit; development of a model of heat and mass transfer processes in multi-stage multistream multiphase systems. The most significant results obtained were: the developed unified methodology for the matrix description of the processes of energy and mass flows’ formation in multicomponent multistream energy systems of the TPP. Within the framework of the proposed methodology, a model of a steam turbine power was developed; model solutions were obtained and analyzed in order to calculate the energy characteristics of a heating turbine unit, the reliability and validity of the proposed approach was shown, a mathematical model of multistream multi-stage heat exchange systems were developed. The significance of the results obtained consisted in the development of a simple but informative mathematical model of a thermal power plant turbine generator and a model of multistream multi-stage heat exchange systems, each stage of which can have an arbitrary number of input and output flows with a possible phase transition in heat carriers.